PENERAPAN SISTEM MONITORING AKTIVITAS AKADEMIK SISWA PADA SMART INTEGRATED ACADEMIC SCHOOL (SIAS) BERBASIS ANDROID DI MTS AL IKHLAS JAMBAR - Neng Sri Lathifah Zulfa; Fanji Fakhru Zaman; Reni Nuraeni (Jurnal Fakultas Teknik Kuningan, 2023)
This research aims to provide convenience to parents or guardians of students in knowingtheir students' academic progress. It also aims to facilitate teachers in conveying students'academic performance information to parents and enable easy monitoring of studentsand discussions with the school authorities. The research uses a qualitative method,where the researcher seeks to describe the process of developing the Smart IntegratedAcademic School monitoring system application. This application was developed usingthe waterfall system development method and programmed in PHP. The results to thisresearch show that the application is capable of providing convenience for parents totrack their students' academic progress. Additionally, the program created also facilitatesparents in easily monitoring their students' progress and engaging in discussions with theschool.